2008
DOI: 10.1089/oli.2008.0131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Polyethylenimine Formulations for Light-Controlled Gene Silencing using Small Interfering RNA Molecules

Abstract: Photochemical internalization (PCI) is a technology based on a photosensitizer that photochemically destabilizes endosomal membranes after illumination, resulting in the release of endocytosed material into the cytosol. In this study, we investigated the potential of using polyethylenimine (PEI) for light-controlled delivery of small interfering RNA (siRNA) molecules via the endocytic pathway. PEI formulations with different molecular weights (MW) and chemical forms (linear [L]/branched [B]) were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…no polycations between 2.5 and 25 kDa) and lack of LDH or similar assays make further interpretation difficult. (Boe S, 2008) In none of these cases the degree of cell membrane disruption has been assessed (i.e. by the lactose dehydrogenase assay), and since the toxicity is clearly due to the disruption and poration of cellular membranes this is clearly a major gap in our knowledge, which will be addressed in the current work.…”
Section: Introductionmentioning
confidence: 99%
“…no polycations between 2.5 and 25 kDa) and lack of LDH or similar assays make further interpretation difficult. (Boe S, 2008) In none of these cases the degree of cell membrane disruption has been assessed (i.e. by the lactose dehydrogenase assay), and since the toxicity is clearly due to the disruption and poration of cellular membranes this is clearly a major gap in our knowledge, which will be addressed in the current work.…”
Section: Introductionmentioning
confidence: 99%
“…When delivering siRNA molecules, care was taken to obtain high endosomal entrapment prior to illumination of the PS. The endosmolytic capacity of B-PEI in combination with S100A4 5¢UTR siRNA molecules under various N/P ratios have been extensively validated in our previous study (Boe et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…NM_002961) were ordered from Eurogentec. The S100A4 5¢UTR siRNA molecules (481-499; 5-UGAGCAA GUUCAAUAAAGA-3, 3-ACUCGUUCAAGUUAUUUCU-5) were chosen based on effective gene silencing in previous studies (Boe et al, 2007(Boe et al, , 2008(Boe et al, , 2010. For the S100A4 5¢UTR siRNA binding site, see Supplementary Fig.…”
Section: Moleculesmentioning
confidence: 99%
“…Polyethylenimine (PEI), a cationic polymer that has been widely used as a nonviral vector (Boe et al, 2008), has previously been used to enhance the transfection efficiencies of magnetic nanoparticles (McBain et al, 2007), such as for the intracellular delivery of plasmid DNA (Huth et al, 2004). However, a recent study reported that PEI shows cytotoxicity and genotoxicity when used as a gene carrier (Choi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%